SEDAR: secured energy efficient destination aware routing protocol in delay tolerant network. (10th April 2015) - Mangrulkar, Ramchandra S.; Atique, Mohammad
Delay tolerant network is highly emerging and competing research area, particularly in an era where the ultimate aim is to provide ubiquitous connectivity, even in diversified regions. Routing with minimum bandwidth and limited energy consumption is a challenging issue thereof. Problem of optimising path is of great deal when energy constraints become the main issue. This paper proposes a secured energy efficient destination aware routing protocol, SEDAR. SEDAR restricts the transmission area by splitting geographical region into various sectors. A direction angle for given destination is computed using global positioning system (GPS) coordinates. Heuristic information at current relay node and predictive inferences based on direction angle are used to obtain optimal trajectory toward the destination. Cooperative neighbour node selection is done based on some computed factors viz. node's trust value and node's residual energy level. SEDAR supports public key cryptographic model to deliberately introduce security issues. Performance of SEDAR is evaluated on map–based movement model. Results obtained prove SEDAR to be energy efficient. Comparative results obtained prove that SEDAR increases packet delivery ratio by 15–30%, decreases routing overhead and also reduces energy consumption by 3–5%. Simulation results establish the correctness of the proposed algorithm.